Relation of serum magnesium level to microvascular complications and the components of metabolic syndrome in patients with type 2 diabetes mellitus - Heba M Yossef; Nashwa S Ghanem; Ula M Al-Jarhi; Ollfat G Shaker (SpringerOpen, 2017)
Background and aim Diabetes mellitus is associated with magnesium (Mg) depletion in intracellular and extracellular compartments. Hypomagnesemia has been suggested to be associated with macrovascular and microvascular complications of diabetes. The effect of the metabolic syndrome (MetS) has markedly increased. Recently, there is increasing evidence that dietary Mg intake and supplementation are inversely associated with the risk for MetS and its components. The aim of this study is to evaluate the relation of Mg level to diabetes, its microvascular complications, and MetS components in Egyptian patients with type 2 diabetes mellitus. Patients and methods The study involved 90 patients older than 35 years who were divided into two groups: 70 patients with type 2 diabetes and 20 patients as control. Patients' group was subdivided into those with complications (neuropathy, retinopathy, and nephropathy) and those without complications. For every patient, history and clinical examination including blood pressure, waist circumference, testing for peripheral neuropathy, and fundus examination were done. Fasting blood sugar (FBS) and 2-h postprandial blood sugar (2-h PPBS), glycated hemoglobin (HbA1c), albumin/creatinine ratio, creatinine level, total cholesterol, high-density lipoprotein-cholesterol, triglycerides, and serum Mg were obtained. Results Serum Mg was significantly lower in diabetic patients than in control (P=0.007). Hypomagnesemia was detected in 56 (80%) patients and none of control. Mg was lower in patients with complications than in patients without; however, the difference was statistically insignificant. Statistically significant negative correlation between serum Mg with serum cholesterol, triglyceride, creatinine level, albumin/creatinine ratio, FBS, 2-h PPBS, and HbA1c was found. Conclusion Hypomagnesemia is prevalent in diabetic patients. It is associated with diabetic complications and poor glycemic control. High plasma triglycerides, total cholesterol, creatinine level, albuminuria, HbA1c, FBS, and 2-h PPBS are independent correlates of hypomagnesemia.